2011
DOI: 10.1093/humrep/der022
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centred infertility care: a qualitative study to listen to the patient's voice

Abstract: BACKGROUND High-quality care for patients faced with infertility should be patient-centred. Few studies have provided in-depth insights into the patient's perspective on care and, to the best of our knowledge, no study has provided a model of the complex concept 'patient-centred infertility care'. Therefore, a qualitative study aimed at understanding 'patient-centred infertility care' from the patient's perspective was conducted. METHODS Fourteen focus group discussions were organized with patients (n = 103) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 46 publications
3
136
0
7
Order By: Relevance
“…2,3 Multiple strategies to promote public involvement in the development of health policies on assisted reproductive technologies need to be used such as arts-based approaches and traditional consultation like consensus panels. 1 Users' empowerment in decision-making processes may be reinforced through more inclusive priority-setting processes including participation in councils on assisted reproductive technologies with at least one member representing IVF couples; and the government should promote increased awareness of infertility through local research projects aiming to address the medical, legal, ethical, social, cultural, psychological and political dimensions of infertility treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Multiple strategies to promote public involvement in the development of health policies on assisted reproductive technologies need to be used such as arts-based approaches and traditional consultation like consensus panels. 1 Users' empowerment in decision-making processes may be reinforced through more inclusive priority-setting processes including participation in councils on assisted reproductive technologies with at least one member representing IVF couples; and the government should promote increased awareness of infertility through local research projects aiming to address the medical, legal, ethical, social, cultural, psychological and political dimensions of infertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,9 This study aimed to evaluate users' reasons for choosing public or private IVF treatment and to identify their suggestions for improving infertility treatment.…”
mentioning
confidence: 99%
“…Participants also felt that communication with clinics was better than in the UK, often with direct and readily available access to the clinician leading their care. Many of these factors have been identified as key components of 'patient-centred fertility care' generally (Dancet et al, 2010;Dancet et al, 2011;Redshaw, Hockley, & Davidson, 2007;Schmidt et al, 2003). A systematic review of patients' perspectives of fertility care concluded that fertility patients 'want to be treated like human beings with a need for: medical skills, respect, coordination, accessibility, information, comfort, support, partner involvement and a good attitude of and relationship with fertility clinic staff' (Dancet et al, 2010, p. 467).…”
Section: It Was a Bit More Daunting There's The Language And Cyrillimentioning
confidence: 99%
“…Regarding patient centeredness, it is surprising that half of the final indicators relate to emotional support provided by counsellors as these concerns only 1 out of 10 dimensions of patient-centred infertility care (Dancet et al, 2011b. However, the need for all staff members to address patients from a psychosocial besides a medical perspective during routine care (Boivin et al, 2001;Dancet et al, 2011b) was addressed by the other two indicators.…”
Section: The Multidimensional Quality Indicator Set For Infertility Carementioning
confidence: 99%